Reconstruction of Grant Contracts on Disaster Donation Distribution through Humanitarian Institutions in Aceh - Fitria Mardhatillah; Sela Azkia; Shira Thani; Nabhani Yustisi; Tasyukur Tasyukur (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
The flash flood disaster in Aceh has had a great social and economic impact, encouraging people to distribute aid through donations. In the perspective of Islamic law, the donation contains elements of a grant contract as a voluntary gift without reward. However, studies on the application of grant contracts in the distribution of disaster donations are still limited, especially related to the validity of ijab kabul in emergency conditions, the typology of mutlaqah and muqayyadah grants, and its conformity with the fiqh of the Shafi'i school and positive law in Indonesia. This study aims to analyze the concept of grant contracts in Islamic law and its relevance to the practice of distributing flood disaster donations in Aceh, as well as examining the suitability of the aid distribution mechanism with the harmony and conditions of the grant contract. The research uses normative legal methods with a conceptual approach and a legislative approach supported by literature studies on classical and contemporary fiqh literature. The results of the study show that the distribution of donations has basically met the elements of wahib, mauhub lah, mauhub, and sighat. In practice, ijab kabul is often carried out implicitly through digital platforms and can still be considered valid as long as it meets the principle of willingness of the parties. The study also found a number of obstacles in the form of weak supervision of aid distribution, unclear status of distributing institutions, and potential deviations in fund management that can reduce the value of the mandate in grant contracts. The contribution of this research lies in the formulation of the concept of the validity of qabdh in disaster emergency conditions as well as the preparation of the typology of grant contracts for disaster donations as a development of contemporary muamalah fiqh. The research recommends standardizing the grant contract mechanism and strengthening the monitoring system based on the principles of trust, accountability, and transparency to realize the benefits of disaster-affected communities.